2014
DOI: 10.1007/s11120-014-9980-0
|View full text |Cite
|
Sign up to set email alerts
|

Engineering cyanobacteria as photosynthetic feedstock factories

Abstract: Carbohydrate feedstocks are at the root of bioindustrial production and are needed in greater quantities than ever due to increased prioritization of renewable fuels and reduction of carbon emissions. Cyanobacteria possess a number of features that make them well-suited as an alternative feedstock crop in comparison to traditional, terrestrial plant species. Recent advances in genetic engineering, as well as promising preliminary investigations of cyanobacteria in a number of distinct production regimes have i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
73
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 99 publications
(74 citation statements)
references
References 89 publications
1
73
0
Order By: Relevance
“…While much research focuses on engineering cyanobacterial metabolism towards the synthesis of end products (e.g., biofuels), cyanobacteria are also under consideration for the production of carbohydrate feedstocks to support fermentative bioindustrial processes [1]. In this approach, cyanobacterial biomass is processed to provide organic carbon [2–6], or cyanobacterial cells are manipulated to secrete simple fermentable sugars [712].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…While much research focuses on engineering cyanobacterial metabolism towards the synthesis of end products (e.g., biofuels), cyanobacteria are also under consideration for the production of carbohydrate feedstocks to support fermentative bioindustrial processes [1]. In this approach, cyanobacterial biomass is processed to provide organic carbon [2–6], or cyanobacterial cells are manipulated to secrete simple fermentable sugars [712].…”
Section: Introductionmentioning
confidence: 99%
“…To provide organic carbon to engineered consortia, we use a Synechococcus elongatus PCC 7942 strain previously engineered to export up to 85% of the carbon it fixes in the form of sucrose [12], a simple sugar also produced by plant-based feedstocks (e.g., sugarcane) that is readily consumed by many microbes. S. elongatus naturally accumulates sucrose as a compatible solute [1, 19], and can export this carbohydrate through heterologous expression of the proton/sucrose symporter, cscB (hereafter cscB + )[12, 20]. Under mild osmotic shock and slightly alkaline conditions, cscB + S. elongatus continuously generate sucrose at up to 36 mg sucrose L −1 hr −1 , a rate predicted to substantially exceed that of sugarcane, if successfully cultivated to scale [12].…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have demonstrated the feasibility of converting energy from sunlight and carbon from CO 2 directly into biofuels using photosynthetic microorganisms (Hays and Ducat, 2015; Oliver and Atsumi, 2014). Cyanobacteria have evolved efficient metabolic processes for harvesting light energy to produce organic molecules, and they can be cultivated in locations that do not compete with food production for land resources (Melis, 2009; Zhu et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…In this explanation, photosynthetic carbon and energy assimilation that can no longer be directed to growth when population increase is inhibited by nutrient deficiency or other stresses results in overflow products, particularly TAG (Du and Benning, 2016). The concept of overflow metabolism has traditionally been associated with the export of metabolites by heterotrophic microbes (Neijssel and Tempest, 1975) and has more recently also been applied to photosynthetic metabolism in cyanobacteria (Hays and Ducat, 2015;Courchesne et al, 2009;Gründel et al, 2012) and higher plants (Weise et al, 2011). In microalgal work, the idea of photosynthetic overflow (excess photosynthetic energy and carbon) as the driver of oil accumulation has become a widely accepted explanation (Hu et al, 2008;Li et al, 2012;Solovchenko, 2012;Li et al, 2013;Klok et al, 2014;Du and Benning, 2016).…”
mentioning
confidence: 99%